PENGARUH OPINI AUDIT DAN PERUBAHAN OPINI AUDIT TERHADAP REPORTING DELAY - Dias Nurmalasari; Dwi Ratmono (Diponegoro Journal of Accounting, 2014)
This research aimed to examine the influence on audit opinion and change in audit opinion of reporting delay. The auditor switch, the new accounting standard, unexpected earnings, leverage and profitability used as control variable. Based on the research variables to develop some hypotheses that the audit opinion better than the previous year will negatively affect on the reporting delay and change in audit opinion better than the previous year will negatively affect on the reporting delay . Samples of this research is 170 manufacture firms listed in Indonesia Stock Exchange in year 2011-2012 that selected by using purposive sampling method. The technique of analysis used for examining the hypothesis was multiple regression. The result of this research that audit opinion and change in audit opinion have negatively significant influenced on the reporting delay variable. Firms that receiving unqualified audit opinion and audit opinion better than the previous year gave a good news for investors so as to reduce the reporting delay.